Marketing Innovation in Partnership with Self Help Groups: A Case Study of a Farm Inputs Manufacturer - Rajan, C. R.; Xavier, M. J. (Indian Journal of Marketing, 2015)
This is a case study of a marketing innovation by a leading fertilizer manufacturing company through a project with self-help groups (SHGs). The project was initiated by the company in 2003 in Andhra Pradesh. Then, the farm input companies were faced with the challenge of meeting the farmers’ requirements on a timely basis. This was largely because of the dominance of distributors and dealers across the supply network. The wholesaler’s loyalties to the companies were limited and opportunistic, and lay with products that gave them more margins and not with what were ideal for farming. The farmers were, as a consequence, also plagued by woes such as non availability of fertilizers during peak cropping seasons, high costs of transportation of fertilizers from the nearest town to remote villages, high interest rates charged by the channel members, opportunistic pricing practiced by distributors, and influx of substandard products. The company, in order to limit the role of the wholesalers and to supply fertilizers directly to the farmers, engaged the self-help group members as direct dealers, simultaneously creating livelihood opportunities for these members. The project engaged as many as 750 groups in the state of Andhra Pradesh. The objective of this research was to draw a case of the project as an example for other corporations to adapt in their respective strategies for business development in rural areas and to alter their mechanisms of distribution and their forms of service for the end consumers.